Synthetic Aperture Ultrasonic Imaging Based on Coded Exciting and Coherence Factor Adaptive Weighting - Chichao Zheng; Hu Peng; Weiyong Zhu; Zhihui Han; Xuexiao Lai (2011 International Conference on Intelligent Computation and Bio-Medical Instrumentation, 2011)
Conference Factor (CF) algorithm is effective to suppress the side lobe of the ultrasonic image except for the far-field. To improve this demerit, a new algorithm Chirp Coherence Factor (Chirp CF) is proposed in this paper. In this method, the chirp signal is transmitted, and the received signals are processed with the pulse compression combined with adaptive weighting of CF. The new method can retain both high signal-to-noise rate (SNR) of the chirp signal and low side-lobe of CF, and at the same time enhance the far field image quality of the traditional CF algorithm benefited from excellent transmission capacity of the coded signal. Simulation results show that the new method can not only achieve a high horizontal resolution, but also improve the contrast, SNR, and the far field image quality.